Effects of Cement Additions on Self-compacting Concrete Durability Indicators - Salhi, Mohamed; Boubekeur, Toufik; Li, Alex; Ghrici, Mohamed (Periodica Polytechnica Civil Engineering, 2022)
This study highlights the effect of initial curing time on sustainability indicators such as sorptivity (S), water absorption (WA) and total porosity (P) of self- compacting concretes (SCC) containing the blended cement such as limestone cement (CEMIIA-L42.5) and pozzolanic cement (CEMII-A-P42.5). The durability test (acid and sulfate attack) of SCCs is also studied in this researcher. For this purpose, three water/binder (W/B) ratios were used, Six SCC mixtures were prepared and tested in the fresh state (slump follow, flow time, J-Ring, L-Box, V-Funnel and sieve segregation), the main properties in the hardened state compressive strength (Sc), S, WA and P of the SCC mixtures were studied and evaluated each in its different curing. Furthermore, the results of the Sc and transfer properties are globally significantly affected by the hot climate during the design and maturation phase. On the other hand, the values of S to SCC for pozzolanic cement are lower compared to limestone cement and this regardless of W/B ratio and the cure mode. The difference between the mixtures SCC-L32, SCC-L38 and SCC-L44 at the 28 day is between 2.45%, 87.57% depending on the cure mode and the W/B ratio. In addition, WA was observed to range from 5.8 to 7.1%. On the other hand, a good correlation was found between sustainability indicators and Sc. Durability has also been improved for pozzolanic cement compared to that of limestone cement as compressive strength against sulfate and acid attack have been improved.
Number: 2
Keywords: acid attack